(untitled) (Research, Society and Development, 2022)
Montrichardia linifera (Arruda) Schott is an aquatic macrophyte of the Araceae family that is widespread in traditional medicine and little explored from a scientific point of view. Therefore, it becomes an excellent species for exploring its biotechnological potential. Therefore, the objective of this research was to carry out a scientific and technological prospection on Montrichardia linifera with a focus on anthelmintic activity. Technological prospecting was carried out by searching for patents in the following bases: EPO, USPTO, DII, INPI and WIPO. The search for scientific works was carried out in the following databases: SciELO, Bireme, Web of Science, Scopus and Science Direct from 2010 to 2022. The results for patents showed that it obtained only 3 (three) publications in the international databases DII and WIPO and in the Brazilian base INPI 2 (two) publications. In the scientific search, a total of 50 (fifty) publications were obtained for the descriptor “Montrichardia linifera”, in all analyzed bases. For the descriptor “Montrichardia linifera” and “anthelmintic” only one publication was obtained. Thus, it is clear that there are still few scientific works related to M. linifera, thus requiring more incentives. However, investments are necessary to carry out more research related to this plant in order to unveil its therapeutic activities.